Performance-Shaping Factors Affecting Older Adults' Hospital-to-Home Transition Success: A Systems Approach. (3rd January 2018) - Werner, Nicole E; Tong, Michelle; Borkenhagen, Amy; Holden, Richard J
Abstract: Background and Objectives: Facilitating older adults' successful hospital-to-home transitions remains a persistent challenge. To address this challenge, we applied a systems lens to identify and understand the performance-shaping factors (PSFs) related older adults' hospital-to-home transition success. Research Design and Methods: This study was a secondary analysis of semi-structured interviews from older adults ( N = 31) recently discharged from a hospital and their informal caregivers ( N = 13). We used a Human Factors Engineering approach to guide qualitative thematic analysis to develop four themes concerning the system conditions shaping hospital-to-home transition success. Results: The four themes concerning PSFs were: (a) the hospital-to-home transition was a complex multiphase process—the process unfolded over several months and required substantial, persistent investment/effort; (b) there were unmet needs for specialized tools—information and resources provided at hospital discharge were not aligned with requirements for transition success; (c) alignment of self-care routines with transition needs—pre-hospitalization routines could be supportive/disruptive and could deteriorate/be re-established; and (d) changing levels of work demand and capacity during the transition—demand often exceeded capacity leading to work overload. Discussion and Implications: Our findings highlight that the transition is not an episodic event, but rather a longitudinal process extending beyond the days just after hospital discharge. Transition interventions to improve older adults' hospital-to-home transitions need to account for this complex multiphase process. Future interventions must be developed to support older adults and informal caregivers in navigating the establishment and re-establishment of routines and managing work demands and capacity during the transition process.